Membrane vesicles in Acidithiobacillia class extreme acidophiles: influence on collective behaviors of ‘Fervidacidithiobacillus caldus’ - Rossoni, Stefano; Beard, Simón; Segura-Bidermann, María Ignacia; Duarte-Ramírez, Juan; Osorio, Francisco Kirhman; Varas-Godoy, Manuel; Martínez-Bellange, Patricio; Vera, Mario; Quatrini, Raquel; Castro, Matías (Frontiers in Microbiology, 2024)
Membrane Vesicles (MVs) are envelope derived extracellular sacs that perform a broad diversity of physiological functions in bacteria. While considerably studied in pathogenic microorganisms, the roles, relevance and biotechnological potential of MVs from environmental bacteria are less well established. Acidithiobacillaceae family bacteria are active players in the sulfur and iron biogeochemical cycles in extreme acidic environments and drivers of the leaching of mineral ores contributing to acid rock/mine drainage (ARD/AMD) and industrial bioleaching. One key aspect to such role is the ability of these bacteria to tightly interact with the mineral surfaces and extract electrons and nutrients to support their chemolithotrophic metabolism. Despite recent advances in the characterization of acidithiobacilli biofilms and extracellular matrix (ECM) components, our understanding of its architectural and mechanistic aspects remains scant.In this work, we show that vesiculation is a common phenomenon in distant members of the Acidithiobacillaceae family, and further explore the role of MVs in multicellular colonization behaviors using `Fervidacidithiobacillus caldus´ as bacterial model. Production of MVs in `F. caldus´ occurred in both planktonic cultures and biofilms formed on sulfur surfaces, where MVs appeared individually or in chains resembling Tube-Shaped Membranous Structures (TSMSs) important for microbial communication. Liquid chromatography-mass spectrometry data and bioinformatic analysis of the MVs-associated proteome revealed that `F. caldus´ MVs were enriched in proteins involved in cell-cell and cell-surface processes, and largely typified the MVs as outer MVs (OMVs). Finally, microbiological assays showed that amendment of `F. caldus´ MVs to cells and/or biofilms affects collective colonizing behaviours relevant to the ecophysiology and applications of these acidophiles providing grounds for their exploitation in biomining.